Regulation of Myofilament Contractile Function in Human Donor and Failing Hearts - McDonald, Kerry S.; Hanft, Laurin M.; Robinett, Joel C.; Guglin, Maya; Campbell, Kenneth S. (Frontiers in Physiology, 2020)
Heart failure (HF) often includes changes in myocardial contractile function. This study addressed the myofibrillar basis for contractile dysfunction in failing human myocardium. Regulation of contractile properties were measured in cardiac myocyte preparations isolated from frozen, left ventricular mid-wall biopsies of donor (n = 7) and failing human hearts (n = 8). Permeabilized cardiac myocyte preparations were attached between a force transducer and position motor and both Ca2+ and sarcomere length (SL) dependence of force, rate of force, loaded shortening, and power output were measured at 15 ± 1°C. Myocyte preparation size was similar between groups (Donor: length, 148 ± 10 µm, width, 21 ± 2 µm, n = 13; HF: length, 131 ± 9 µm, width, 23 ± 1 µm, n = 16). Maximal Ca2+ activated isometric force also was similar between groups (Donor: 47 ± 4 kN·m-2; HF: 44 ± 5 kN·m-2), which implicates previously reported force declines in multicellular preparations reflect, at least in part, tissue remodeling. Maximal force development rates also were similar between groups (Donor: ktr = 0.60 ± 0.05 s-1; HF: ktr = 0.55 ± 0.04 s-1), and both groups exhibited similar Ca2+ activation dependence of ktr values. Human cardiac myocyte preparations exhibited a Ca2+-activation dependence of loaded shortening and power output. Peak power output normalized to isometric force (PNPO) decreased ~12% from maximal Ca2+ to half-maximal Ca2+ activations in both groups. Interestingly, SL dependence of PNPO was diminished in failing myocyte preparations. During submaximal Ca2+ activation, a reduction in SL from ~2.25 µm to ~1.95 µm caused a ~26% decline in PNPO in donor myocytes but only a ~11% change in failing myocytes. These results suggest that altered length dependent regulation of myofilament function impairs ventricular performance in failing human hearts.